Effects of cold stratification on the endogenous hormone, dormancy and germination of Cornus walteri Wanger seeds - Donglin, Li; Yaquin, Jin; Chengjing, Yu; Yuan, Xue (Bangladesh Journal of Botany, 2020)
The most critical phase in plant life is the germination period, which is influenced by both intrinsic and environmental factors. Assessment of cold stratification on several endogenous hormone, IAA, abscisic acid (ABA), gibberellin GA1/3 (GA1/3), zeatin-riboside (ZRs) and isopen-tenyl adenine (iPAs), and germination of Cornus walteri Wanger. seeds was done. Relationship between endogenous hormone and seed germination and mechanism of seed dormancy of C. walteri were also analysed. The results showed that the significant fluctuatation of both IAA and iPAs content was fond during cold stratification period, while the variation of ZRs was little, that of both ABA and GAs content increased with old stratification days. Effects of cold stratification on both GR and GP were significant (p < 0.05), which play an important role in releaving of seed germination and improving seed germination. The GR and GP were significantly negatively correlated with the contents of ABA and GA1/3, and positively correlated with the following iPAs, ZRs/ABA, iPAs/ABA.